The role of the renin‐angiotensin system in skin physiology and pathophysiology - Silva, Igor Maciel Souza; Assersen, Kasper Bostlund; Willadsen, Natalie Nanette; Jepsen, Julie; Artuc, Metin; Steckelings, Ulrike Muscha (Experimental dermatology, 2020)
Since its first description around the year 2000, the local renin‐angiotensin system (RAS) in skin has been subject of an increasing number of studies with many additions over the last two to three years. A focus of research has been investigations on the role of cutaneous angiotensin receptors and locally synthesised angiotensin II in wound healing, in dermatoses associated with skin fibrosis and in melanoma. This review will provide an introduction into the RAS with emphasis on information relevant for the cutaneous RAS. It will discuss the role of the RAS in skin physiology, followed by a detailed review of the existing literature addressing the role of local angiotensin II and angiotensin AT1 and AT2 receptors in wound healing and in various skin diseases such as hypertrophic scars/keloids, scleroderma, dystrophic epidermolysis bullosa, Dupuytren's disease, squamous cell carcinoma, melanoma and psoriasis. In a final section, the potential relevance of drugs, which interfere with the RAS, for future therapy of dermatological disorders is discussed. Collectively, research about the RAS in skin can currently be described as an area, which has gained increasing attention by basic researchers, thus resulting in a multitude of preclinical studies pointing to the potential relevance of components of the RAS as drug targets in dermatological diseases. With a few small clinical studies already performed successfully for indications such as hypertrophic scars and keloids, it can be said that the skin RAS is now in the critical phase of translation from preclinical evidence to clinical use.